Kinetics of 1- and 2-methylallyl + O2 reaction, investigated by photoionisation using synchrotron radiation. Issue 2 (6th January 2021) - Schleier, Domenik; Reusch, Engelbert; Gerlach, Marius; Preitschopf, Tobias; Mukhopadhyay, Deb Pratim; Faßheber, Nancy; Friedrichs, Gernot; Hemberger, Patrick; Fischer, Ingo
Abstract : The reaction kinetics of the isomers of the methylallyl radical with molecular oxygen has been studied in a flow tube reactor at the vacuum ultraviolet (VUV) beamline of the Swiss Light Source storage ring. Abstract : The reaction kinetics of the isomers of the methylallyl radical with molecular oxygen has been studied in a flow tube reactor at the vacuum ultraviolet (VUV) beamline of the Swiss Light Source storage ring. The radicals were generated by direct photodissociation of bromides or iodides at 213 nm. Experiments were conducted at room temperature and low pressures between 1 and 3 mbar using He as the buffer gas. Oxygen was employed in excess to maintain near pseudo-first-order reaction conditions. Concentration–time profiles of the radical were monitored by photoionisation. For the oxidation of 2-methylallyl (2-MA) and with k (2-MA + O2 ) = (5.1 ± 1.0) × 10 11 cm 3 mol −1 s −1, the rate constant was found to be in the high-pressure limit already at 1 mbar. In contrast, 1-methylallyl exists in two isomers, E - and Z -1-methylallyl. We selectively detected the E -conformer as well as a mixture of both isomers and observed almost identical rate constants within the uncertainty of the experiment. A small pressure dependence is observed with the rate constant increasing from k (1-MA + O2 ) = (3.5 ± 0.7) × 10 11 cm 3 mol −1 s −1 at 1 mbar to k (1-MA + O2 ) = (4.6 ± 0.9) × 10 11 cm 3 mol −1 s −1 at 3 mbar. While for 2-methylallyl + O2 no previous experimental data are available, the rate constants for 1-methylallyl are in agreement with previous work. A comparison is drawn for the trends of the high-pressure limiting rate constants and pressure dependences observed for the O2 recombination of allylic radicals with the corresponding reactions of alkyl radicals.